THE INFLUENCE OF INCOME LEVEL, RELIGIOSITY, AND SOCIAL ENVIRONMENT ON MUZAKKI'S DECISION TO PAY ZAKAT - Siti Jamilah; Silvia Amelia (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The purpose of this study was to analyze and identify the influence of the independent variables, such as the level of income, religiosity, and social environment on muzakki's decision to pay zakat, especially for the people of Karang Tengah sub-district, Tangerang City. The method used in this research is field research with a quantitative approach. Samples taken were 100 respondents using the Nonprobability Sampling technique, which was Pusposive Sampling. The analytical method used is SPSS version 24 as a validity test, reliability test, classic assumption test which includes normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, R2 test, hypothesis test containing t test (partial) and F test (simultaneous). Based on the results of the research, it is shown that each independent variable, which is the level of income, religiosity, and social environment has a positive and significant influence on muzakki's decision to pay zakat. And the level of income, religiosity, and social environment together or simultaneously have an impact on the dependent variable, which is the muzakki decision to pay zakat.